Disadvantaged nomadic tribes of Jammu and Kashmir in the frame of livelihood security through animal rearing - WANI, M H; BABA, S H; BAZAZ, NASEER HUSSAIN; ZARGER, BILAL A; BHAT, ARSHAD (The Indian Journal of Animal Sciences, 2019)
This study was conducted to examine various disadvantages associated with livelihood of nomadic tribes and role of animal rearing in their upliftment in Jammu and Kashmir. It was found that majority of nomadic families belonged to very small flock size category and the number declined towards large flock size category. The results revealed that nomadic families took up one of the combinations of economic activities available to them, though animal domestication has been their dominant livelihood option. The estimates of linear function indicated land holding size, literacy, income from other sources and mortality as the significant determinants of livestock possession. The nomadic tribes experienced various kinds of disadvantages and among them mortality of animals was more severe and was observed maximum in large flock size category. The government spending under sub-tribal plans for the development of this section of society has received a setback in recent years. The findings of the study emphasized upon concerted efforts for redressal of the problems and sustainable upliftment of nomadic tribes.